2018
DOI: 10.1080/00380237.2018.1484251
|View full text |Cite
|
Sign up to set email alerts
|

Income Inequality and Chronic Health Conditions: A Multilevel Analysis of the U.S. States

Abstract: Recently, much scholarly work has been conducted examining the effect of rising income inequality on health outcomes. However, this work is somewhat inconclusive. Chiefly, the mechanisms which could produce such an association are still being sorted out. Further, much of this work is focused on mortality outcomes with little attention to how this process operates for actual health conditions, including chronic health problems, which are arguably now the main public health concerns of the developed world. In th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Although not a direct test, our results are also generally consistent with the noted principles of Power, Proximity, and Physiology. Past research shows that income inequality undermines the health and functioning of populations (Anderson et al, 2018, Clarkwest, 2008, Diez-Roux et al, 2000, Hill and Jorgenson, 2018, Lynch et al, 2001, Kaplan et al, 1996, Kawachi and Kennedy, 1999, Neumayer and Plümper, 2016; Pickett & Wilkinson, 2015; Rambotti, 2015; Wen et al, 2003; Wilkinson and Pickett, 2006, Wilkinson and Pickett, 2009). While we observe an inverse relationship between income inequality and life expectancy, we also provide additional evidence to suggest that income inequality can amplify the health risks associated with environmental degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not a direct test, our results are also generally consistent with the noted principles of Power, Proximity, and Physiology. Past research shows that income inequality undermines the health and functioning of populations (Anderson et al, 2018, Clarkwest, 2008, Diez-Roux et al, 2000, Hill and Jorgenson, 2018, Lynch et al, 2001, Kaplan et al, 1996, Kawachi and Kennedy, 1999, Neumayer and Plümper, 2016; Pickett & Wilkinson, 2015; Rambotti, 2015; Wen et al, 2003; Wilkinson and Pickett, 2006, Wilkinson and Pickett, 2009). While we observe an inverse relationship between income inequality and life expectancy, we also provide additional evidence to suggest that income inequality can amplify the health risks associated with environmental degradation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we expand on previous health research and environmental justice research by exploring the health implications of the intersection of air pollution and income inequality in the US context (Charafeddine & Boden, 2008). Although previous scholarship has shown that greater income inequality is associated with poorer population health (Anderson et al, 2018, Clarkwest, 2008, Curran and Mahutga, 2018, Diez-Roux et al, 2000, Hill and Jorgenson, 2018, Lynch et al, 2001, Kaplan et al, 1996, Kawachi and Kennedy, 1999, Neumayer and Plümper, 2016; Pickett & Wilkinson, 2015; Rambotti, 2015; Wen, Browning, & Cagney, 2003; Wilkinson and Pickett, 2006, Wilkinson and Pickett, 2009), in this study we are less interested in the direct effects of income inequality on health. Instead, we consider whether air pollution is especially detrimental to the health of US states’ populations characterized by the inequitable distribution of income.…”
Section: Introductionmentioning
confidence: 94%
“…In addition to the different illness risks, the recovery will be felt unequally across groups, highlighting the link between health and economic inequalities (Anderson, Bjorklund, and Rambotti 2019; Hill and Jorgenson 2018; Sharma 2020). Canadians who happened to be unemployed and looking for work as the pandemic hit faced a dramatic decrease in job vacancies, as high as a 50 percent decline in the number of jobs available (Bell and Blanchflower 2020; Jones et al 2020).…”
Section: Covid-19 Health Disability and Employmentmentioning
confidence: 99%
“…A related body of research reveals direct associations between income inequality and worsened population health outcomes (e.g., Anderson, Bjorklund, and Rambotti 2019; Mishra and Carleton 2015; Pickett and Wilkinson 2015), including reduced life expectancy (e.g., Chetty et al 2016; Hill and Jorgenson 2018; Thombs et al 2020). Inequality directly affects population health because relative deprivation in living standards is associated with lower social-emotional outcomes, maladaptive coping mechanisms, and lower subjective well-being (Oishi, Kesebir, and Diener 2011; Payne, Brown-Iannuzzi, and Hannay 2017; Wilkinson and Pickett 2010).…”
Section: Ghg Emissions Income Inequality and Human Well-being In The ...mentioning
confidence: 99%